2009
DOI: 10.1095/biolreprod.108.075481
|View full text |Cite
|
Sign up to set email alerts
|

Human Villous Trophoblasts Express and Secrete Placenta-Specific MicroRNAs into Maternal Circulation via Exosomes1

Abstract: In this study, we performed small RNA library sequencing using human placental tissues to identify placenta-specific miRNAs. We also tested the hypothesis that human chorionic villi could secrete miRNAs extracellularly via exosomes, which in turn enter into maternal circulation. By small RNA library sequencing, most placenta-specific miRNAs (e.g., MIR517A) were linked to a miRNA cluster on chromosome 19. The miRNA cluster genes were differentially expressed in placental development. Subsequent validation by re… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

13
388
0
6

Year Published

2011
2011
2021
2021

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 436 publications
(413 citation statements)
references
References 38 publications
13
388
0
6
Order By: Relevance
“…Although it has been in argument and discussion on reference strategies for normalizing circulating miRNAs, there is still no consensus (Ma et al, 2012). 5s rRNA, U6 snRNA, and miR‐16 are frequently used as internal normalization controls (Luo et al., 2009; Pineles et al, 2007; Zhao et al., 2010). In this study, U6 snRNA showed low abundance in the plasma samples.…”
Section: Resultsmentioning
confidence: 99%
“…Although it has been in argument and discussion on reference strategies for normalizing circulating miRNAs, there is still no consensus (Ma et al, 2012). 5s rRNA, U6 snRNA, and miR‐16 are frequently used as internal normalization controls (Luo et al., 2009; Pineles et al, 2007; Zhao et al., 2010). In this study, U6 snRNA showed low abundance in the plasma samples.…”
Section: Resultsmentioning
confidence: 99%
“…In this study, we demonstrated that maternal BMI is a factor that explains for >20% of 401 the observed variation in plasma exosomes concentration (Figure 3 has not been established, however, the levels of placental miRNA, which are secreted 434 from placental cells into exosomes, decrease dramatically after delivery [51]. of exosomes (100 µg/ml) isolated from plasma obtained from lean, overweight (OW), 687…”
Section: A C C E P T E D Accepted Manuscriptmentioning
confidence: 88%
“…Recent studies have demonstrated that functional miRNAs are also horizontally transferred via this mechanism. The presence of a miRNA pool has been reported in exosomes and shedding vesicles derived from a variety of sources, including mast cells (Valadi et al, 2007), blood (Hunter et al, 2008), stem cells (Yuan et al, 2009;Collino et al, 2010), adipocytes (Ogawa et al, 2010;Müller et al, 2011), syncytiotrophoblasts (Luo et al, 2009) and milk (Hata et al, 2010). Valadi et al pioneered the description of the so-called "exosomal shuttle miRNA," showing that exosomes isolated from a mouse mast cell line MC/9, a human mast cell line HMC-1 and from primary bone marrow-derived mast cells contain substantial miRNA populations (Valadi et al, 2007).…”
Section: Microvesicle-mediated Mirna Transfermentioning
confidence: 99%
“…However, the biological significance of miRNAs derived from adipocyte microvesicles remains uncertain at this moment. In a different system, Luo et al hypothesized that syncytiotrophoblasts secrete miRNAs into maternal circulation via exosomes (Luo et al, 2009). In an attempt to prove this hypothesis, they isolated exosomes from the villous trophoblast model cell line, BeWo.…”
Section: Microvesicle-mediated Mirna Transfermentioning
confidence: 99%
See 1 more Smart Citation